2012
DOI: 10.7439/ijpc.v2i3.800
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Telmisartan and Forced Degradation Behavior by Rp-HPLC in Tablet Dosage Form

Abstract: A simple, rapid, precise, sensitive and reproducible reverse phase high performance liquid chromatographic (RP-HPLC) method for determination of Telmisartan (TELM) in tablet dosage form was developed and validated. Chromatographic separation was achieved on a 250 × 4.6 mm, 5µ, Waters symmetry column in gradient mode, with mobile phase consisting of a mixture of solution (10 mM potassium dihydrogen phosphate, pH 3.5 ± 0.01): acetonitrile (64:40) was used. The quantitation performed at flow rate of 1.0 mL/min at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…As per literature review, many published data were found regarding forced degradation of TEL alone by UV, 21 HPLC 22,23 and simultaneous estimation of TEL along with other class of antihypertensive drugs, 24,25 diuretics. 26 Very few numbers of papers are available, that utilizes HPTLC method for the estimation of TEL.…”
Section: Introductionmentioning
confidence: 99%
“…As per literature review, many published data were found regarding forced degradation of TEL alone by UV, 21 HPLC 22,23 and simultaneous estimation of TEL along with other class of antihypertensive drugs, 24,25 diuretics. 26 Very few numbers of papers are available, that utilizes HPTLC method for the estimation of TEL.…”
Section: Introductionmentioning
confidence: 99%
“…It is a diabetes angiotensin receptor blocker that shows high affinity for the angiotensin II type 1 (AT1) receptors, has a long duration of action, and has the longest half-life of any angiotensin II receptor blocker (ARB) [1]. In clinical studies, Telmisartan shows comparable antihypertensive activity to other major antihypertensive classes, such as angiotensin converting enzyme (ACE) inhibitors, beta-blockers, and calcium antagonists [2].…”
Section: Introductionmentioning
confidence: 99%
“…TELMI blocks the vasoconstrictor and aldosterone secreting effects of angiotensin II by selectively blocking the binding of angiotensin II to the AT1 receptor in many tissues, such as vascular smooth muscle and the adrenal gland [2,3]. TELMI has been estimated by various methods like spectrophotometric [4], HPLC [5,6], HPTLC [7][8][9][10], and LC-MS [11,12] in pharmaceutical formulations and biological fluids.…”
Section: Introductionmentioning
confidence: 99%